Algorithm for the Management of Patients with Ischemic Heart Disease and Cardio-Renal-Metabolic Syndrome - Yevhen Yu. Marushko; Georgii B. Mankovskyi (Ukrainian Journal of Cardiovascular Surgery, 2025)
Cardiorenal-metabolic syndrome (CRMS) is the most dangerous combination of heart failure, chronic kidney disease, and type 2 diabetes mellitus, as it combines comorbidities, each of which is a powerful proatherogenic factor.Aim. To assess the prognostic impact of using a new algorithm for managing patients with CAD and CRMS over a 5-year follow-up period.Materials and methods. In a prospective study, we included 377 patients with coronary artery disease and cardiorenal-metabolic syndrome. Patients underwent invasive coronary angiography. In case of insignificant coronary lesions, CFRi was determined to establish microvascular angina, which was treated with medication. In the case of a single-vessel stenotic coronary lesion, PCI was performed. In the case of a two- or three-vessel lesion, PCI or CABG/MCS was performed depending on the Syntax Score. Patients were followed for 5 years from the moment of initial hospitalization.Results. The total number of endpoints achieved in the entire cohort of patients with CHD and CRMS (cardiovascular death, myocardial infarction, need for repeated revascularization) was 104 (30.3%) of the 343 patients who completed the study. Interestingly, 79 (76.0%) of them reached the endpoint due to the formation of new stenosis in the coronary arteries. At the same time, the use of the algorithm for selecting revascularization tactics in patients with CAD and CRMS resulted in the need for repeated intervention due to restenosis of previously installed stents in only 3 (2.7%) of 111 PCI cases.Conclusions. In patients with cardiorenal-metabolic syndrome, the cause of coronary artery disease in 17.5% of cases is microvascular angina, while in 82.5% – stenosing atherosclerosis of coronary vessels. The risk of angina recurrence in patients with coronary artery disease and CRMS within 5 years after primary treatment is 30.3%, of which – in 76.0% of cases due to the formation of new coronary artery lesions. The use of the proposed algorithm for myocardial revascularization tactics in patients with CAD and CRMS allows achieving a frequency of significant restenosis of previously installed coronary stents in only 2.7% of cases during a 5-year follow-up.